Nexus between population growth and economic growth a provincial-level analysis using Philippine data - Cayanga, Juan Luis F. (School of Economics, University of the Philippines Diliman, 2019)
Numerous studies have shown mixed results on the effect of population changes on the economic growth of a country. In this paper, we try to estimate changes in wealth brought about by different contraceptive consumption behaviors in the Philippines using provincial_level data from the National Demographic and Health Survey years 2008, 2013, and 2017. By using Ordinary Least Squares, we find that an increase in the proportion of women using contraceptives in a Philippine province at a previous time period has a positive and significant effect on a province_s current average wealth. We also find that contraceptive use reduces the provincial average gap between a household_s desired and actual family size, depending on the predicted number of children. These findings strengthen certain sections of the Reproductive Health Law concerning wider provision of contraceptives.